Measuring the Impact of Economic Variables on the Stock Market in Saudi Arabia: An Analytical Study from 2000 – 2021 - Basilim, Ahmad Saeed; Balila, Basel Yasser (Journal of Economic, Administrative and Legal Sciences, 2024)
The goal of this paper is to measure the impact of some major macroeconomic variables on the market value of the Saudi stock market during the period from 2000 to 2021. To achieve this, we used the ARDL model to examine the relationship between the market value of the stock market as a dependent variable and a set of macroeconomic variables as independent variables. These independent variables include oil prices, economic growth, bank credit to private sector, money supply, and interest rates. Both a descriptive and an econometric analysis methods were followed in which the independent variables were analyzed to test the main hypothesis that there is statistically significant impact of the selected macroeconomic variables on the market value of the Saudi stock market during the period from 2000 to 2021. The results showed statistically significant and positive effects of oil prices, money supply, economic growth, and bank credit to private sector on the market value of the Saudi stock market. The results also showed a statistically significant and negative effect of interest rates on the market value of the Saudi Stock market. The value of the error correction term (ECT) indicates that the dependent variable quickly returns to its long-term equilibrium value. In conclusion, this paper emphasizes the importance of a continuous monitoring of these macroeconomic variables and recommends taking the necessary measures to reduce their negative impact on the stock market in Saudi Arabia.